Hubungan Antara Pemanfaatan Sumber Belajar dengan Prestasi Belajar Siswa Kelas Tinggi SDN 116 Timurung Kecamatan Ajangale Kabupaten Bone - adnan, K adnan, K; Suhrin Fajrin; Muh. Idris Jafar (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This research is a quantitative research with the type of correlational research which aims to determine whether there is a significant relationship between Learning Resources and Student Achievement at SDN 116 Timurung, Ajangale District, Bone Regency. All students in grades IV, V and VI of SDN 116 Timurung, Ajangale District, Bone Regency, totaling 58 students. The sampling technique in this study used a probabilin sampling technique, namely simple random sampling. The research data were obtained by collecting data through questionnaires. The data analysis technique used statistic descriptive and inferential analysis. Based on the results of inferential statistical analysis, value of rcount (0,376) is greater than the value of rtable (0,256) at a significance of 5%. It can be concluded that there is a significant relationship between learning resources and high grade students' achievement at SDN 116 Timurung, Ajangale District, Bone Regency